Pulmonary functional imaging (PFI): A historical review and perspective. (January 2023) - Bozovic, Gracijela; Schaefer-Prokop, Cornelia M; Bankier, Alexander A
PFI Pulmonary Functional Imaging (PFI) refers to visualization and measurement of ventilation, perfusion, gas flow and exchange as well as biomechanics. In this review, we will highlight the historical development of PFI, describing recent advances and listing the various techniques for PFI offered per modality. Challenges PFI is facing and requirements for PFI from a clinical point of view will be pointed out. Hereby the review is meant as an introduction to PFI.